Race-Conscious Career Development: Exploring Self-Preservation and Coping Strategies of Black Professionals in Corporate America. Issue 4 (November 2020) - Sisco, Stephanie
The Problem: Corporations have maintained a history of operating as racialized social systems that contribute to racial divisions and inequities in the workplace. Despite this reality, there have been high-achieving Black men and women who have overcome limitations and unfavorable circumstances. In this study, resilience to racial bias in corporate America is explored through the lived experience of Black professionals by using a phenomenological research method. The Solution: Race, racism, and workplace incivility are discussed in a conceptual framework to examine how racial bias still exists in the workplace and to contextualize the participants' experiences. As a result of the findings, self-preservation and coping strategies are identified to provide insight into how the participants overcame social and racial barriers that influence their professional identities and career development in corporate America. The Stakeholders: This research is intended to inform organizational leaders and career development researchers and specialists who are invested in the advancement of Black professionals and the communities they represent. This study also has implications for human resource developers and researchers who seek to minimize racial bias against Black professionals through racial discourse and race-conscious research.